Evaluation of medication safety resources in pediatric hospitals. (20th August 2020) - Nelson, Kembral L; Morvay, Shelly; Neidecker, Marjorie; Sebastian, Sonya; Fischer, Jessica; Li, Junan; Pai, Vinita; Merandi, Jenna
Abstract: Purpose: As health systems continue to expand pharmacy and clinical services, the ability to evaluate potential medication safety risks and mitigate errors remains a high priority. Workload and productivity monitoring tools for the assessment of operational and clinical pharmacy services exist. However, such tools are not currently available to justify medication safety pharmacy services. The purpose of this study is to determine methods used to assess, allocate, and justify medication safety resources in pediatric hospitals. Methods: A 32-question survey was designed and distributed utilizing the Research Electronic Data Capture (REDCap) tool. The survey was disseminated to 46 pediatric hospitals affiliated with the Children's Hospital Association (CHA). The survey was distributed in October 2018, and the respondents were given 3 weeks to submit responses. Data analysis includes the use of descriptive statistics. Categorical variables were summarized by frequencies and percentages to distinguish the differences between pediatric health systems. Results: Of 26 respondents, 15.4% utilized metrics to justify medication safety resources. Metrics utilized were based on medication dispenses, projects, and error coding. Twenty-three percent of respondents were dissatisfied with current pharmacy-based medication safety resources within the organization. There was variability of medication safety resources within pediatric hospitals, including the number of dedicated full-time equivalents, time spent on tasks, and task prioritization. Conclusion: Assessing medication safety resources at various pediatric hospitals highlights several potential barriers and opportunities. This information will serve as the foundation for the creation of a standardized workload assessment tool to assist pharmacy leaders with additional resource justification.